Effectiveness of Dhikr Istighfar in Reducing OSCE-Related Anxiety among Medical Students - Sari, Imelda Purnama; Oktariza, Rury Tiara; Indriyani, Indriyani; Tanzila, Raden Ayu; Zalika, Putri; Noviyanti, Noviyanti (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2025)
Background: The prevalence of anxiety among medical students is still relatively high, including in Objective Structured Clinical Examinations (OSCE). This anxiety will have an impact on students' academic achievement. Relaxation techniques can be used to overcome anxiety incidents, and dhikr is a form of relaxation activity. Purposes: This research aimed to determine the decrease in student anxiety about the OSCE exam by dhikr istighfar. Methods: The method used in this research was quasi-experimental research with a pre-posttest and control group design. The research subjects were students of the Muhammadiyah University Palembang first-semester medical study program who would undergo the OSCE block exam and were willing to participate in this research through informed consent. Result: Research data analysis showed that comparison between pretest and posttest for each group also showed significant differences (P < 0.001). It means that dhikr istighfar is significantly effective in reducing students’ anxiety, especially during OSCCE. Conclusion: In conclusion, Dhikr Istighfar may be used as an anxiety management tool in medical education to overcome the anxiety level of students who will take exams, especially OSCE.